1990
DOI: 10.1017/s0031182000061308
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) in British soils

Abstract: SUMMARYSoil from 403 hedgerow, roadside verge, woodland, heathland or field sites was assessed for presence of entomopathogenic rhabditid nematodes with aGalleria larva baiting technique. Steinernematids were recovered from 48 % of the sites but only one site yielded Heterorhabditis sp. The species recovered most frequently was Steinernema bibionis (Bovien). Another unidentified Steinernema sp. was also isolated. Prevalence of steinernematids in the different types of habitat formed continuum so that roadside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 10 publications
5
45
0
2
Order By: Relevance
“…Brown and Gaugler (1997) demonstrated that drought can markedly delay EPN emergence from host cadavers. There is some evidence of seasonality of occurrence in different EPN surveys (Mráček, 1980;Akhurst & Bedding, 1986;Blackshaw, 1988;Hominick & Briscoe, 1990). By contrast, Campbell et al (1995) and Glazer (1996) reported an absence of seasonal fluctuation in EPN densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown and Gaugler (1997) demonstrated that drought can markedly delay EPN emergence from host cadavers. There is some evidence of seasonality of occurrence in different EPN surveys (Mráček, 1980;Akhurst & Bedding, 1986;Blackshaw, 1988;Hominick & Briscoe, 1990). By contrast, Campbell et al (1995) and Glazer (1996) reported an absence of seasonal fluctuation in EPN densities.…”
Section: Discussionmentioning
confidence: 99%
“…However, biotic and abiotic factors cause the distribution EPN to differ across different regions. Factors such as soil texture, temperature and host availability are thought to be important in determining their distribution (Hominick & Briscoe, 1990;Griffin et al, 1991;Stock et al, 1999).…”
Section: Entomopathogenic Nematodes (Epn) Frommentioning
confidence: 99%
“…Both genera have global distributions and numerous surveys have documented their occurrence in Australia (Akhurst & Bedding, 1986), Europe (e.g. Mráček, 1980;Vänninen et al, 1989;Hominick & Briscoe, 1990;Griffin et al, 1991) and the Americas (e.g. Mráček & Webster, 1993;Liu & Berry, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Dead larvae are washed in distilled water and put on White's trap for extraction or dissected out to see the presence of nematodes. The coloration of dead larvae gives some indication about the presence of EPNs (Hominick and Briscoe, 1990). Annual medium temperature and rainfall had little association with the presence of nematode, Heterorhabditis indicus isolated from soils in Tamil Nadu (Poinar et al, 1992).…”
Section: Introductionmentioning
confidence: 95%